Circulating vascular progenitor cells and central arterial stiffness in polycystic ovary syndrome. - Cecile Dessapt-Baradez; Maria Reza; Ghayathri Sivakumar; Maria Hernandez-Fuentes; Kostas Markakis; Luigi Gnudi; Janaka Karalliedde (PLoS ONE)
Objective Subjects with Polycystic ovarian syndrome (PCOS) are at increased risk of Type 2 diabetes mellitus (T2DM). The mechanism of this enhanced risk is unclear. Circulating vascular progenitor cells (VPC) are immature bone marrow derived cells capable of differentiating into mature endothelial cells. VPC number/function and central arterial stiffness predict cardio-metabolic disease in at-risk populations. Design We studied VPC and arterial stiffness measures in non-obese PCOS subjects as compared to age and body mass index (BMI) matched healthy controls in a cross-sectional study. Methods Fourteen subjects with PCOS and 12 controls of similar age, BMI (all <30 kg/m(2)) and metabolic profile were studied. VPC number and in vitro function were studied by flow cytometry and tube formation assays respectively. Augmentation index (AIx), a measure of central arterial stiffness, and central (aortic) blood pressures (BP) were measured by applanation tonometry. Results Subjects with PCOS had a reduced number, mean±SEM, of circulating CD34(+)133(+) VPCs (317.5±51.0 vs. 558.3±101.2, p = 0.03) and impaired in vitro tube formation (completed tube area 1.0±0.06 vs. 1.2±0.05×10(6) µm(2) p = 0.02). PCOS subjects had significantly higher AIx (18.4±1.9% vs. 4.9±2.0%) and this difference remained significant even after adjustments for age, BMI and smoking (p = 0.003) in multivariate analyses. Central systolic and pulse pressure were higher in PCOS subjects but these differences were not statistically significant after adjustment for age. Brachial systolic and pulse pressures were similar. VPC number/function and arterial stiffness or BP measures were not correlated. Conclusions Non-obese PCOS is characterized by a reduced VPC number, impaired VPC function and increased central arterial stiffness. These changes in novel vascular risk markers may explain the enhanced risk of T2DM and CVD in PCOS.